Workload analysis to determine the optimal number of workforce using the Work Load Analysis (WLA) method at PT. Harapan Jaya Multi Bisnis - Ahmad, Arfandi; Herdianzah, Yan; Safutra, Nur Ihwan; Rauf, Nurhayati; Gamgulu, Rifki; Nur, Taufik (OPSI, 2023)
Workload is something that arises due to excessive activity demands. The workload is not proportional to the number of available workers because of the high target of pipe production while the number of workers is lacking so that human resources cannot work productively, especially in the production department at PT. Harapan Jaya Multi Bisnis. The purpose of this study is to determine the workload of employees in pipe production and determine the optimal number of workers. This study uses the Work Load Analysis (WLA) method to analyze the workload in determining the optimal number of workers. The results of this study after calculating the workload, it is proposed that the fixed cutting section is 2 people with a workload of 62.65%. In Branding, in real terms there is 1 person with a total workload of 11.73% and an average workload of 11.73%. After calculating the workload, it is proposed that the shooting section still be 1 person with a workload of 11.73%, because if additional workers are added, the workload will be too low. The time needed to complete the activity is 7 hours per day. After calculating the workload, Quality Control is proposed to be 1 person, because if additional workers are added, the workload will be too low, namely 7 hours per day.